Biochemical analysis of the saliva extracted from two different leech species - Habeeb, Batool K.; Al-Warid, Harith Saeed (Iraqi Journal of Science, 2025)
Leech saliva contains numerous compounds, primarily consisting of proteins and peptides. This research focused on two leech species, Hirudo verbana and Hirudo orientalis, which were obtained from various alternative medicine clinics and scientific centers located in Baghdad, Iraq. Saliva samples were collected from the leehches after 5 and 6 weeks of food deprivation. Bradford proteins assay, UV absorption technique, Gel electrophoresis and RP-HPLC were used to analyze their saliva chemically. Anticoagulant activity of their saliva was also assessed using prothrombin time assay. Results showed that the concentration of saliva proteins were higher in the 5 weeks of starvation than the concentration of proteins in the 6 weeks of starvation for both species. The gel electrophoresis analysis revealed the presence of up to 16 distinct bands. Three molecular weights were found to be closely related to known proteins from leech species through comparison of the gel electrophoresis data with the literatures. Additional proteins found in the saliva extract by gel electrophoresis may possibly be associated to totally new biologically active proteins and peptides in the saliva extract or to a modification (isoforms) of the present ones or to a mixture of both. It was found that the crude saliva secretions of both H. verbana and H. orientalis have anticoagulant activity. The active action of H. verbana was stronger than the H. orienralis. The means of prothrombin time for H. verbena were higher than the means of prothrombine time for H. orientalis although no significant differences were noticed between them.